Connecting language needs in the workplace to the learning of English at tertiary level - Talif, Rosli; Noor, Rohimmi (Universiti Putra Malaysia Press, 2009)
Fresh graduates, it seems, lack confidence and have poor communication and English proficiency skills that could affect their employabiIity (JobStreet.com, 2005). This paper investigates the relevance of the tertiary English language proficiency curriculum to the workplace. It is to find out if the respondents, who were mostly in the final year of their studies, are adequately prepared to use English at the workplace. This study involved four public tertiary institutions of higher learning in Malaysia. A total of 86 final year students, who were involved in industry-linkage programmes that lasted between four and six months, agreed to participate in this exercise. They came from diverse academic fields such as computer science, engineering, architecture, accounting, science, economics, communication, business, and ICT. Structured interview sessions were carried out and analysed based on content analysis. Brief descriptions about the English programmes offered at the respective tertiary institutions and comments by the respondents about the courses were also considered. Ideally, the desired outcome of any English proficiency programme is a student who can perform adequately in English in the workplace environment and is able to carry out minimum office routines such as writing brief reports, taking minutes, as well as performing formal and informal oral interactions.